2021
DOI: 10.1159/000515058
|View full text |Cite
|
Sign up to set email alerts
|

Total Dietary Fat Intake, Fat Quality, and Health Outcomes: A Scoping Review of Systematic Reviews of Prospective Studies

Abstract: <b><i>Introduction:</i></b> We conducted a scoping review of systematic reviews (SRs) on dietary fat intake and health outcomes in human adults within the context of a position paper by the “International Union of Nutritional Sciences Task force on Dietary Fat Quality” tasked to summarize the available evidence and provide dietary recommendations. <b><i>Methods:</i></b> We systematically searched several databases for relevant SRs of randomized controlled trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 98 publications
1
28
0
Order By: Relevance
“…As expected, the results of the present study suggested that RO and BO oils reduce the serum LDL‐C and NEFA concentrations of rats compared with the feeding of CO oils when included in normal and high‐fat diets. This might be because of the low SFA content and high MUFA content of the RO and BO oils 31,32 . Consistent with this finding, Bumrungpert et al 33 .…”
Section: Discussionsupporting
confidence: 52%
“…As expected, the results of the present study suggested that RO and BO oils reduce the serum LDL‐C and NEFA concentrations of rats compared with the feeding of CO oils when included in normal and high‐fat diets. This might be because of the low SFA content and high MUFA content of the RO and BO oils 31,32 . Consistent with this finding, Bumrungpert et al 33 .…”
Section: Discussionsupporting
confidence: 52%
“…However, the intake of ruminant TFA was not related to all-cause mortality and CHD, but inversely associated with risk of T2D [50]. Results from the above mentioned meta-analyses and other SRs [51] indicate that the identified guidelines were not always in line with current evidence, for which reason it may be assumed that quantitative thresholds for dietary fat intake are often subjective, and a continued limited on these fats is not always justified [52]. Dietary guidelines inform consumers on adequate nutrition (i.e., energy density) and health promotion and aim to reduce the burden of noncommunicable diseases in a population by modifying dietary intake.…”
Section: Comparison With Findings From Systematic Reviewsmentioning
confidence: 81%
“…However, the available evidence was insufficient to establish whether there is a difference between ruminant and industrial TFAs consumed in equivalent amounts on the risk of CHD (EFSA NDA Panel, 2010c). Recent systematic reviews and meta-analyses confirm the positive association between the intake of total and industrial TFA and risk of CHD, whereas the relationship appears to be null for TFA from ruminant sources (Bendsen et al, 2011;de Souza et al, 2015;Schwingshackl et al, 2021). The available evidence, however, remains insufficient to establish whether industrial and ruminant TFA have different effects on CHD risk when consumed in equivalent amounts (Bendsen et al, 2011;de Souza et al, 2015).…”
Section: Trans Fatty Acidsmentioning
confidence: 99%